Ticagrelor versus prasugrel in diabetic patients with an acute coronary syndrome - Laine, Marc; Frere, Corinne; Toesca, Richard; Berbis, Julie; Barnay, Pierre; Pansieri, Michel; Michelet, Pierre; Bessereau, Jacques; Camilleri, Elise; Ronsin, Olivia; Helal, Olfa; Paganelli, Franck; Dignat-George, Françoise; Bonello, Laurent (Thrombosis and Haemostasis, 2014)
Optimal P2Y12 receptor blockade is critical to prevent ischaemic recurrence in patients undergoing percutaneous coronary intervention (PCI). We aimed to compare the level of platelet reactivity (PR) inhibition achieved by prasugrel and ticagrelor loading dose (LD) in diabetic acute coronary syndrome (ACS) patients undergoing PCI. We performed a single-center prospective open-label randomised trial. Patients with diabetes mellitus undergoing PCI for an ACS were randomised to receive prasugrel 60 mg or ticagrelor 180 mg. The primary endpoint of the study was the level of platelet reactivity (PR) assessed between 6 and 18 hours post-LD using the VASP index. We randomised 100 diabetic patients undergoing PCI for an ACS. No difference was observed in baseline characteristics between the two groups. In particular, the rate of patient receiving insulin therapy was identical (25 vs 28.6%; p =0.7). Ticagrelor achieved a significantly lower PR compared to prasugrel loading dose (17.3 ± 14.2 vs 27.7 ± 23.3%; p=0.009). In addition the rate of high on-treatment platelet reactivity, defined by a VASP ≥50%, tend to be lower in the ticagrelor group although the difference did not reach statistical significance (6 vs 16%; p=0.2). The rate of low on treatment PR was identical (60 vs 54%; p=0.8). The present study demonstrates that ticagrelor LD is superior to prasugrel LD to reduce PR in ACS patients with diabetes mellitus. Whether the higher potency of ticagrelor could translate into a clinical benefit should be investigated.
Keywords: VASP index; P2Y12 receptor blockade; acute coronary syndrome; diabetes mellitus; percutaneous coronary intervention